INDEPENDENT NEWS WEB SITES’ COVERAGE OF RELIGION IN CENTRAL ASIA - FREEDMAN, Eric; WALTON, Maureen (CENTRAL ASIA AND THE CAUCASUS, 2006)
The five Central Asian governments tightly control religious freedom and practices. Most mass media remain state-owned or tightly controlled, and journalists exercise self-censorship, with or without official censorship. One result is a dearth of reporting by domestic media about religious freedom issues, which are culturally and politically sensitive for these authoritarian regimes. Western-based Web news sites like those of the Institute for War and Peace Reporting (www. iwpr.net), EurasiaNet (www.eurasianet.org), and IRIN News (www.irinnews.org) provide alternative venues for independent reporting on news about religion, but access to these sites is difficult or impossible for most people. Central Asian journalists who report for these sites confront challenges and risks. Religion in Central Asia is inextricably interwoven with politics. All five governments are secular in orientation and practice, although some leaders wrap themselves in religious mantles for political purposes. These regimes worry not only about violent fundamentalism but also about the prospect of Islamist parties that may threaten the incumbents’ hold on power. In the case of Kazakhstan, for example, “the extremist Islamist political organization Hizb ut-Tahrir is banned, and its members are subject to arrest and imprisonment for subversion,” according to the U.S. State Department.1 One expert observed that national leaders have used campaigns against “radical Islam” as a pretext to oust local figures and centralize political control.2